Lei de Acesso à Informação e Transparência: proposta de inclusão de informações no portal Transparência UFPB - Almeida, Saulo Eduardo de Carvalho. (2015)
The information in the context in which society currently lives, known as the information society is becoming increasingly value, incurring importance in the daily lives of people as never before reached. In this context, there is the pursuit of Brazilian society in reaching a level of more mature democracy where citizens can be more involved in the State's actions, particularly in the monitoring of public politics and actions. Following a worldwide trend, Brazil seeks to structure a network that citizens can have greater access to government information through the obligation of public agencies and entities to create and maintain transparency portals, which has the task of seeking a closer relationship between the government and the population. In this sense, the research proposed the adequacy of the transparency portal of the Federal University of Paraíba to the Access to Information Act, to include all the information specified as mandatory by legal rules above, as well as inclusion of possible innovative initiatives taken by other institutional portals such, of to enable this important instrument for democracy can come to fulfill their important role in society.